2018
DOI: 10.1016/j.apsusc.2018.05.172
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of AlCrFeCoNiCu high-entropy alloy by pulsed laser deposition

Abstract: Pulsed laser deposition has been used to prepare thin films of the high entropy alloy AlCrFeCoNiCu. The 35 nm films were deposited in ultra-high vacuum onto glass at room temperature and above and analysed using X-ray diffraction and X-ray photoelectron spectroscopy. Films deposited at room temperature exhibit a mix of FCC and BCC reflections, the FCC crystallites having size similar to the film thickness, but the BCC crystallites are larger. The intensity of the reflections from both crystal structures reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…These techniques are suitable for the formation of solid‐solution HEMs but require very high heating temperatures. The last method is gas‐phase synthesis, which includes molecular beam epitaxy, 74 atomic layer deposition, 75 and pulsed laser deposition 76 . Sophisticated and complex instruments are needed for this method, and the productivity of HEMs is not easy to promote.…”
Section: Novel Strategies For Synthesis Of Heas and Hecsmentioning
confidence: 99%
“…These techniques are suitable for the formation of solid‐solution HEMs but require very high heating temperatures. The last method is gas‐phase synthesis, which includes molecular beam epitaxy, 74 atomic layer deposition, 75 and pulsed laser deposition 76 . Sophisticated and complex instruments are needed for this method, and the productivity of HEMs is not easy to promote.…”
Section: Novel Strategies For Synthesis Of Heas and Hecsmentioning
confidence: 99%
“…Figure 29a shows the schematic of PLD components. An intense pulsed laser beam has concentrated on the target materials whereupon the materials are vaporized into flux of fragments material, and deposited on the substrate material as thin film under the chamber either filled with background gas [86] or high vacuum atmosphere [16,87] to avoid any type of contaminations or interactions. On the other hand, PLD considers fast thin film technique (10-15 min) with high quality compared to other methods.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
“…However, the uneven concentration of target material on the substrate occurs and hence it may not be suitable for large scale film growth. M. Cropper [16] prepared a thin film of AlCrFeCoNiCu on borosilicate glass by PLD. Results showed that large crystal sizes of both FCC and BCC phase structures were obtained at room temperature.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, increasing the graphene oxide content improved the corrosion resistance of the coating, mainly by improving the composition segregation of the HEA. Crooper et al prepared an AlCrFeCoNiCu HEA film via pulsed laser deposition [11]. This film comprised BCC and FCC phases, with a larger crystal size of the BCC phase when compared with that of the FCC phase.…”
Section: Introductionmentioning
confidence: 99%